Sosialisasi Vaksinasi dan Pembagian Sembako pada Masa Pandemi di Desa Cangakan, Wironanggan, Gatak, Sukoharjo - Makhabbah Jamilatun; Ria Istiqomah (Abdimas Mandalika, 2022)
Abstract:  Covid-19 is an infectious disease caused by the coronavirus. WHO has declared Covid-19 a pandemic. The Covid-19 pandemic has become one of the toughest periods for all countries experiencing it, including Indonesia. The government has taken various measures by issuing regulations to deal with the Covid-19 pandemic. In addition to implementing health protocols, the government has implemented a policy of vaccinating Covid-19. Even though the vaccination program has been carried out, some people still have doubts about vaccines, it can be said that people do not understand the use of vaccines. Based on this description, community service activities were carried out regarding the socialization of Covid-19 vaccination in Cangakan villages, Wironanggan, Gatak, Sukoharjo, and distribution of necessities to surrounding communities who were undergoing independent isolation. The method of activity used in this community service activity uses several stages, namely a survey of the target group, identification of program needs, preparation of facilities and infrastructure, implementation, and evaluation. The results of this community service activity are that residents in Cangakan Village, Wironanggan, Gatak, Sukoharjo have come to understand the covid-19 vaccination and understand the importance of covid-19 vaccination as an effort to prevent covid-19, and by distributing necessities to the surrounding community can help ease the burden on residents. affected by the Covid-19 pandemic.Abstrak: Covid-19 merupakan penyakit menular yang disebabkan oleh virus corona. WHO telah menetapkan Covid-19 sebagai pandemi. Pandemi Covid-19 menjadi salah satu periode yang berat bagi semua negara yang mengalaminya, termasuk Indonesia. Berbagai cara dilakukan pemerintah dengan mengeluarkan aturan untuk menanggulangi pandemi Covid-19. Selain penerapan protokol kesehatan, pemerintah menerapkan kebijakan melakukan vaksinasi Covid-19. Meskipun program vaksinasi sudah dilakukan, masih terdapat keraguan pada sebagian masyarakat terhadap vaksin, bisa dikatakan masyarakat belum paham mengenai kegunaan vaksin. Berdasarkan uraian tersebut, maka dilakukan kegiatan pengabdian kepada masyarakat mengenai sosialisasi vaksinasi covid-19 di Desa Cangakan, Wironanggan, Gatak, Sukoharjo dan pembagian sembako pada masyarakat sekitar yang sedang menjalani isolasi mandiri. Metode kegiatan yang digunakan dalam kegiatan pengabdian kepada masyarakat ini dengan menggunakan beberapa tahapan, yaitu survei kelompok sasaran, identifikasi kebutuhan program, persiapan sarana dan prasarana, pelaksanaan dan evaluasi. Hasil kegiatan pengabdian kepada masyarakat ini adalah warga di Desa Cangakan, Wironanggan, Gatak, Sukoharjo menjadi paham tentang vaksinasi covid-19 dan paham pentingnya vaksinasi covid-19 sebagai upaya pencegahan covid-19, dan dengan pembagian sembako pada masyarakat sekitar dapat membantu meringankan beban warga yang terdampak pandemi covid-19.